Problem-Based Learning dalam Matematika Sekolah Menengah Kejuruan (SMK) Berbasis Masalah Kontekstual: Systematic Literature Review - Rendrayana, Ketut; Suparta, I Nengah; Suharta, I Gusti Putu (Media Pendidikan Matematika, 2026)
Problem-Based Learning (PBL) is a pedagogical approach that fosters critical thinking, problem-solving skills, and contextual understanding. This Systematic Literature Review (SLR) examines the characteristics, effectiveness, challenges, and contextual integration of PBL in mathematics teaching and learning at vocational high schools. Using the PRISMA method, a total of 186 articles were retrieved from the ScienceDirect, Google Scholar, and ResearchGate databases. After applying strict inclusion criteria focusing exclusively on mathematics learning in peer-reviewed journal articles, 15 articles were selected for in-depth analysis. The findings indicate that PBL consistently improves critical thinking skills, mathematical problem-solving abilities, conceptual understanding, and mathematical literacy in vocational high school contexts. Key challenges include teachers’ readiness to design industry-aligned mathematical problems, the absence of workplace-context-based mathematics teaching materials, and time constraints. A critical research gap was identified: mathematics textbooks and teaching modules for vocational high schools are generally not designed based on workplace-context principles, particularly for the Hospitality Program, limiting meaningful connections between mathematics learning and industry practices and hindering deep learning. Future research should prioritize the development of industry-integrated mathematics modules that bridge Problem-Based Learning and workplace environments to enhance the relevance and authenticity of vocational mathematics learning.